EDUKASI PENCEGAHAN KEKERASAN SEKSUAL SEBAGAI UPAYA PREVENTIF PERLINDUNGAN DIRI BAGI SISWA SMP NEGERI 1 KONAWE SELATAN - Fatma Wati; Sri Khayati (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Sexual violence against children is a crime that has gained significant public concern in Indonesia, as cases have become an escalating emergency with annual increases. Children, who should ideally receive affection and protection from families and society, are frequently victims of sexual violence. This vulnerability is driven by various factors, including an inability to protect themselves, a lack of sexual education, media influence, and complex social dynamics. Victims often suffer from psychological trauma, declining academic performance, and mental health issues such as depression and anxiety. This community service activity at SMP Negeri 1 Konawe Selatan serves as a preventive measure to help students understand the importance of body autonomy. The activity employed a qualitative-descriptive method, emphasizing an actual and systematic socialization process. During the face-to-face implementation phase, students were equipped with the ability to identify private body areas, the courage to assertively say